PERLINDUNGAN KONSUMEN DALAM TRANSAKSI BAY’ AL-SALAM DAN E-COMMERCE (Komparasi Hukum Islam dan Hukum Positif) - Syaichoni, Ahmad (Ahkam: Jurnal Hukum Islam, 2015)
In the modern era, people utilize technology product to ease thetransaction process, namely e-business or e-commerce. Businessalways includes the producers and consumers. In such business, theconsumers do not get maximum service and sometimes are fooledby the producers. Such kind of business in Islam is known as bay’ alsalam. The transaction in bay’ al salam is prone to tricky acts by theproducers. Therefore, it is urgent to develop a legal contract betweenthe producers and consumers to obtain good transaction between thetwo parties.Kata kunci: Perlindungan Konsumen, Bay’ al-Salam, E-Commerce,Hukum Islam, dan Hukum Positif